Ultraviolet aging resistant asphalt-based composite material and preparation method thereof
By using UV-resistant aging additives such as graphite phase carbon nitride in asphalt matrix composites, the problem of ultraviolet aging of asphalt pavement in high altitude areas of the plateau is solved, and the performance and life of the pavement under strong ultraviolet radiation conditions is significantly improved.
Patent Information
- Application Number
- CN202510026230.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-11
AI Technical Summary
The ultraviolet aging problem of asphalt pavement in high altitude areas of the plateau leads to deterioration of pavement performance and shortening of service life. Existing single ultraviolet aging additives such as nanotitanium dioxide and nano zinc oxide have poor photocatalytic activity and segregation agglomeration problems.
Graphite phase carbon nitride, photoresponse activity accelerator, compatible agent and pH adjuster are used as ultraviolet aging-resistant additives. Ultrasonic dispersion and mechanical stirring treatment, combined with high-speed shear technology, an ultraviolet aging-resistant asphalt matrix composite material is prepared.
It significantly improves the UV aging resistance of asphalt matrix composites, extends the service life of asphalt pavement in high altitude areas of the plateau, and solves the problem of separating additives in the thermal processing stage.
Smart Images

Figure CN119799022A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of road engineering and relates to an ultraviolet aging resistant asphalt-based composite material and a preparation method thereof. Background Art
[0002] Asphalt has become one of the most utilized materials for pavement due to its excellent physical and chemical properties. However, asphalt, a polymer material, will always age during use, leading to deterioration of pavement performance and accelerated crack expansion. Therefore, asphalt aging has always been a hot issue in the field of road engineering materials. Asphalt will inevitably experience thermal oxidative aging and ultraviolet aging in complex service environments. Among them, high-altitude plateau areas pose greater challenges to the service performance and life of asphalt pavements due to strong ultraviolet radiation.
[0003] Due to the large seasonal temperature differences in plateau and high-altitude areas, the service time in high-cold environments often accounts for a high proportion of the annual cycle. Therefore, thermal oxidation aging is no longer the dominant mode of aging of asphalt pavements. UV aging has become one of the key factors affecting the performance and service life of asphalt pavements in plateau and high-altitude areas. Long-term and high-intensity ultraviolet radiation will cause asphalt molecules to transition to excited states with higher activity and lower reaction energy barriers, accelerating the asphalt aging reaction. Asphalt materials deteriorate in performance due to UV aging, which is usually manifested as a weakening of low-temperature crack resistance, fatigue resistance and self-healing ability. Under the multiple effects of fatigue loads and water erosion, the appearance and development of asphalt pavement diseases such as cracks, potholes, looseness and peeling are accelerated, resulting in a reduction in the service life of asphalt pavements.
[0004] At present, the use of ultraviolet absorbers to improve the anti-ultraviolet aging ability of asphalt has attracted much attention, among which nano titanium dioxide (TiO 2 ) and nano zinc oxide (ZnO) have shortcomings such as poor photocatalytic activity and limited visible light response range. In addition, nano metal oxide materials also have problems of segregation and agglomeration in asphalt binders. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and to provide a UV-resistant asphalt-based composite material and a preparation method thereof. The material has excellent UV-resistant performance and can overcome the problem of UV-resistant degradation affecting the service performance and life of asphalt pavement.
[0006] To achieve the above-mentioned purpose, the present invention discloses a UV-resistant asphalt-based composite material, comprising a matrix asphalt and a UV-resistant additive, wherein the UV-resistant additive comprises graphite phase carbon nitride, a photoresponsive activity promoter, a compatibilizer and a pH regulator.
[0007] Further, the mass ratio of the base asphalt to the UV-resistant aging additive is (92-98):(2-8);
[0008] The mass ratio of graphite phase carbon nitride, photoresponsive activity promoter, compatibilizer and pH regulator is (58-70): (15-25): (10-20): (0.5-1.5).
[0009] Furthermore, the pH regulator is concentrated ammonia water.
[0010] Furthermore, the compatibilizer is dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride.
[0011] Furthermore, the photoresponsive activity promoter includes bismuth vanadate and tourmaline powder, and the mass ratio of bismuth vanadate to tourmaline powder is 4:(2-3).
[0012] The invention discloses a method for preparing a UV-resistant asphalt-based composite material, comprising the following steps:
[0013] 1) Weighing matrix asphalt, graphite phase carbon nitride, photoresponsive active accelerator, compatibilizer and regulator;
[0014] 2) dissolving the phase carbon nitride and the photoresponsive activity promoter in an ethanol solution, and then performing ultrasonic dispersion to obtain a dark green solution;
[0015] 3) adding a pH adjuster dropwise to adjust the pH value of the solution, adding a compatibilizer, mechanically stirring, filtering and drying to obtain an anti-ultraviolet aging additive;
[0016] 4) The base asphalt is heated, and then an anti-ultraviolet aging additive is added, and then high-speed shearing is performed to obtain an anti-ultraviolet aging asphalt-based composite material.
[0017] Furthermore, in step 2), the temperature of ultrasonic dispersion is 25-30° C., and the ultrasonic dispersion time is 30-35 min.
[0018] Furthermore, in step 3), the temperature of mechanical stirring is 40-50°C, and the temperature of drying treatment is 70-80°C.
[0019] Furthermore, the mechanical stirring time in step 2) is 1-2h.
[0020] Further, the specific process of step 4) is:
[0021] The base asphalt is heated to 150-160° C., an anti-ultraviolet aging additive is added, and then high-speed shearing is performed at a rotation speed of 2000-2500 rpm for 60-90 minutes to obtain an anti-ultraviolet aging asphalt-based composite material.
[0022] The present invention has the following beneficial effects:
[0023] In the specific operation of the UV-resistant asphalt-based composite material and the preparation method thereof, the graphite phase carbon nitride used in the present invention has a high photoresponse activity and can convert the absorbed ultraviolet energy into chemical energy. The energy conversion caused by this photoresponse activity reduces the transition of valence electrons in the asphalt molecules to the excited state under ultraviolet radiation, which helps to inhibit the aging reaction of the asphalt molecules. In addition, the bismuth vanadate in the added photoresponse activity promoter is coupled with the graphite phase carbon nitride to form a heterojunction, which promotes the mobility of photogenerated carriers and expands the specific surface area. The addition of tourmaline powder further reduces the band gap and expands the photoresponse activity to the visible light region, which greatly improves the light energy conversion efficiency of the UV-resistant additive and enhances the aging inhibition of asphalt molecules in the UV-visible light range. Finally, the UV-visible-near infrared reflectance spectrum results show that the UV-resistant additive with the compatibilizer still maintains a high light energy conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0025] Figure 1 The present invention is a flow chart for preparing the UV-resistant aging additive;
[0026] Figure 2 The UV-visible-near infrared reflection spectra of the UV-resistant aging additives obtained in Examples 1 to 3;
[0027] Figure 3 The fatigue cycle number histogram of the purple aging-resistant asphalt-based composite material obtained in Example 4 to Example 7 under different load-strain conditions;
[0028] Figure 4 The aging factor variation trend diagram of the ultraviolet aging-resistant asphalt-based composite materials obtained in Examples 4 to 7 based on the modulus variation before and after ultraviolet light;
[0029] Figure 5 The infrared spectra of the ultraviolet aging-resistant asphalt-based composite materials obtained in Example 4 to Example 7 before ultraviolet aging;
[0030] Figure 6 The infrared spectra of the ultraviolet aging-resistant asphalt-based composite materials obtained in Examples 4 to 7 after ultraviolet aging;
[0031] Figure 7 This is a trend chart of the aging index change of the ultraviolet aging-resistant asphalt-based composite materials obtained in Examples 4 to 7 based on the changes of carbonyl and sulfoxide groups before and after ultraviolet. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] In the description of the present invention, it should be understood that the terms “include” and “comprises” indicate the presence of described features, wholes, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, wholes, steps, operations, elements, components and / or collections thereof.
[0034] It should also be understood that the terms used in the present specification are only for the purpose of describing specific embodiments and are not intended to limit the present invention. As used in the present specification and the appended claims, unless the context clearly indicates otherwise, the singular forms "a", "an" and "the" are intended to include plural forms.
[0035] It should be further understood that the term "and / or" used in the present specification and the appended claims refers to any combination of one or more of the associated listed items and all possible combinations, and includes these combinations. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in the present invention generally indicates that the associated objects are in an "or" relationship.
[0036] It should be understood that, although the terms first, second, third, etc. may be used to describe preset ranges, etc. in the embodiments of the present invention, these preset ranges should not be limited to these terms. These terms are only used to distinguish preset ranges from each other. For example, without departing from the scope of the embodiments of the present invention, the first preset range may also be referred to as the second preset range, and similarly, the second preset range may also be referred to as the first preset range.
[0037] The word "if" as used herein may be interpreted as "at the time of" or "when" or "in response to determining" or "in response to detecting", depending on the context. Similarly, the phrases "if it is determined" or "if (stated condition or event) is detected" may be interpreted as "when it is determined" or "in response to determining" or "when detecting (stated condition or event)" or "in response to detecting (stated condition or event)", depending on the context.
[0038] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can usually be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0039] Various structural schematic diagrams of the embodiments disclosed in the present invention are shown in the accompanying drawings. These figures are not drawn to scale, and some details are magnified and some details may be omitted for the purpose of clear expression. The shapes of various regions and layers shown in the figures and the relative sizes and positional relationships therebetween are only exemplary, and may deviate in practice due to manufacturing tolerances or technical limitations, and those skilled in the art may additionally design regions / layers with different shapes, sizes, and relative positions according to actual needs.
[0040] The UV-resistant asphalt-based composite material of the present invention includes a matrix asphalt and a UV-resistant additive, wherein the UV-resistant additive includes graphite phase carbon nitride, a photoresponsive activity promoter, a compatibilizer and a pH regulator, wherein the mass ratio of the matrix asphalt to the UV-resistant additive is (92-98): (2-8).
[0041] The mass ratio of graphite phase carbon nitride, photoresponsive activity promoter, compatibilizer and pH regulator is (58-70): (15-25): (10-20): (0.5-1.5).
[0042] In this embodiment, the compatibilizer is dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride.
[0043] In this embodiment, the photoresponsive activity promoter is bismuth vanadate and tourmaline powder, and the mass ratio of bismuth vanadate to tourmaline powder is 4:(2-3).
[0044] In this embodiment, the pH adjuster is concentrated ammonia water.
[0045] The method for preparing the ultraviolet aging resistant asphalt-based composite material of the present invention comprises the following steps:
[0046] 1) Weighing graphite phase carbon nitride, photoresponsive active promoter, compatibilizer and regulator;
[0047] 2) dissolving the phase carbon nitride and the photoresponsive activity promoter in an ethanol solution, and then performing ultrasonic dispersion to obtain a dark green solution;
[0048] 3) adding a pH adjuster dropwise to adjust the pH value of the solution, adding a compatibilizer and then mechanically stirring for 1-2 hours, filtering and drying to obtain an anti-ultraviolet aging additive;
[0049] 4) The base asphalt is heated to 150-160° C., an anti-ultraviolet aging additive is added, and then high-speed shearing is performed at a rotation speed of 2000-2500 rpm for 60-90 minutes to obtain an anti-ultraviolet aging asphalt-based composite material.
[0050] In this embodiment, the temperature of ultrasonic dispersion in step 2) is 25-30° C., and the ultrasonic dispersion time is 30-35 min.
[0051] In this embodiment, the temperature of mechanical stirring in step 3) is 40-50°C, and the temperature of drying treatment is 70-80°C.
[0052] It should be noted that the present invention has the following characteristics:
[0053] Graphite phase carbon nitride has high photoresponsiveness and can absorb ultraviolet rays and convert the absorbed ultraviolet energy into chemical energy, using its own photocatalytic activity to avoid the rapid breakage of asphalt molecular chains and aging reactions; at the same time, the addition of photoresponsive activity promoter improves the photocatalytic ability and photoresponsiveness range of graphite phase carbon nitride, further improving the additive's resistance to ultraviolet aging; in addition, the addition of compatibilizer solves the problem of segregation of the above-mentioned inorganic photocatalytic additives during the preparation and thermal processing stages of asphalt-based materials, providing a basis for the ultraviolet aging-resistant additives to play an efficient role.
[0054] The UV-resistant asphalt-based composite material prepared by using UV-resistant additives has good fatigue resistance and UV-resistant ability, which is beneficial to resist the performance degradation of asphalt pavement under strong UV radiation conditions and improve the service life.
[0055] Embodiment 1
[0056] The preparation method of the graphite phase carbon nitride type UV resistant aging additive described in this embodiment comprises the following steps:
[0057] The crucible containing melamine powder was placed in a muffle furnace at 550° C. and calcined for 4 hours. The sample was taken out and cooled to 20° C., and then ground to obtain a light yellow powder material, namely, a graphite phase carbon nitride type UV resistant aging additive.
[0058] Embodiment 2
[0059] The preparation method of the graphite phase carbon nitride + light-responsive active accelerator type UV-resistant aging additive described in this embodiment comprises the following steps:
[0060] 60 parts of graphite phase carbon nitride, 25 parts of bismuth vanadate and 15 parts of tourmaline powder are placed in 100 ml of ethanol solution, and ultrasonic dispersion and mechanical stirring are carried out to obtain a dark green solution. After precipitation, filtration and drying, a graphite phase carbon nitride + light-responsive active promoter type ultraviolet aging resistant additive is obtained.
[0061] Embodiment 3
[0062] The preparation method of the graphite phase carbon nitride + photoresponsive active promoter + compatible agent type UV aging resistant additive described in this embodiment comprises the following steps:
[0063] 59 parts of graphite phase carbon nitride, 20 parts of bismuth vanadate and 5 parts of tourmaline powder are placed in 100 ml of ethanol solution and subjected to ultrasonic dispersion treatment to obtain a dark green solution. 1 part of pH regulator is added dropwise, and then 15 parts of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride (40% methanol solution) are added. After precipitation, filtration and drying, graphite phase carbon nitride + photoresponsive active promoter + compatible agent type UV aging resistant additive is obtained. The preparation process is as follows: Figure 1 shown.
[0064] Embodiment 4
[0065] The method for preparing the ultraviolet aging resistant asphalt-based composite material described in this embodiment comprises the following steps:
[0066] Heat 98 parts of base asphalt (the asphalt is 90# petroleum asphalt with a needle penetration of 88 at 25°C) to 150-160°C, add 2 parts of UV-resistant additives (graphite phase carbon nitride + photoresponsive active promoter + compatibilizer), and high-speed shear for 60 minutes at a rotation speed of 2000-2500rpm to obtain a UV-resistant asphalt-based composite material.
[0067] Embodiment 5
[0068] The method for preparing the ultraviolet aging resistant asphalt-based composite material described in this embodiment comprises the following steps:
[0069] Heat 96 parts of base asphalt (the asphalt is 90# petroleum asphalt with a needle penetration of 88 at 25°C) to 150-160°C, add 4 parts of UV-resistant additives (graphite phase carbon nitride + photoresponsive active promoter + compatibilizer), and high-speed shear for 60 minutes at a rotation speed of 2000-2500rpm to obtain a UV-resistant asphalt-based composite material.
[0070] Embodiment 6
[0071] The method for preparing the ultraviolet aging resistant asphalt-based composite material described in this embodiment comprises the following steps:
[0072] Heat 94 parts of base asphalt (the asphalt is 90# petroleum asphalt with a needle penetration of 88 at 25°C) to 150-160°C, add 6 parts of UV-resistant additives (graphite phase carbon nitride + photoresponsive active promoter + compatibilizer), and high-speed shear for 60 minutes at a rotation speed of 2000-2500rpm to obtain a UV-resistant asphalt-based composite material.
[0073] Embodiment 7
[0074] The method for preparing the ultraviolet aging resistant asphalt-based composite material described in this embodiment comprises the following steps:
[0075] Heat 92 parts of base asphalt (the asphalt is 90# petroleum asphalt with a needle penetration of 88 at 25°C) to 150-160°C, add 8 parts of UV-resistant additives (graphite phase carbon nitride + photoresponsive active promoter + compatibilizer), and high-speed shear for 60 minutes at a rotation speed of 2000-2500rpm to obtain a UV-resistant asphalt-based composite material.
[0076] Performance Testing
[0077] The UV-visible-near infrared reflectance spectrum test was performed on the UV-resistant aging additives of Example 1 to Example 3, and the test wavelength range was 200-800 nm.
[0078] The UV-resistant asphalt-based composite materials obtained in Examples 4 to 7 were subjected to a linear amplitude scanning test. The test samples were asphalt-based composite materials after short-term thermal oxidative aging. The test temperature was 19°C.
[0079] The UV-resistant asphalt-based composite materials obtained in Example 4 to Example 7 were subjected to short-term thermal oxidative aging (RTFOT) and UV aging (UV) tests.
[0080] Among them, short-term thermal oxygen aging is to place 35g±0.5g of asphalt sample in an aging bottle, place it in a rotary thin film oven preheated to 163°C, maintain high temperature for 75 minutes and rotate and blow. After the test, a short-term aged asphalt sample is obtained.
[0081] UV aging is to place 20g±0.5g of asphalt sample that has undergone short-term thermal oxidation aging in an aging dish with a diameter of 140mm±1mm. The thickness of the asphalt film is about 1mm. The asphalt sample is irradiated with simulated sunlight for 100 hours in an environment of 60°C. The power of the sunlight simulation lamp is 300W.
[0082] Dynamic shear rheology test was performed on the samples of the UV-resistant asphalt-based composite materials obtained in Examples 4 to 7 before and after UV aging. The test mode was temperature scanning, and the test temperature range was 40-80°C. The anti-aging ability of the UV-resistant asphalt-based composite materials can be characterized by comparing the modulus changes of the asphalt samples before and after UV aging. The aging factor calculation formula based on the modulus change is:
[0083]
[0084] Where MAI is the modulus aging factor, M aged is the modulus of asphalt sample after UV aging, M unaged is the modulus of asphalt sample before UV aging.
[0085] The larger the value of the modulus aging factor, the greater the difference in modulus between the asphalt sample before and after UV aging, and the weaker the sample's ability to resist UV aging.
[0086] The samples of the UV-resistant asphalt-based composite materials obtained in Examples 4 to 7 before and after UV aging were subjected to infrared spectroscopy testing, with the test wavelength range being 4000-400 cm -1 The anti-aging ability of UV-resistant asphalt-based composite materials was characterized by comparing the changes in special functional groups (carbonyl and sulfoxide groups) of asphalt samples before and after UV aging. The calculation formulas for the carbonyl aging index (ICO) and the sulfoxide aging index (ISO) are as follows:
[0087]
[0088]
[0089] Test Results
[0090] UV-Vis-NIR reflectance spectroscopy test
[0091] The reflectivity of three UV-resistant additives to light in the wavelength range of 200-800 nm was obtained by testing: Figure 2 As shown. The maximum light response wavelength and bandgap width of the anti-ultraviolet aging additive are shown in Table 1. Compared with the inorganic non-metallic photocatalytic material graphite phase carbon nitride, the anti-ultraviolet aging additive prepared by the present invention has a maximum light response wavelength increased by 14.99% under the action of the light response activity promoter, and the bandgap width is reduced from 2.64eV to 2.33eV, which increases the electron-hole pairs, is beneficial to the absorption and conversion of light energy, and reduces the influence of ultraviolet radiation on asphalt aging and degradation.
[0092] Table 1
[0093]
[0094] Linear amplitude sweep test
[0095] The linear amplitude scanning test results of the UV-resistant asphalt-based composite materials obtained in Example 4 to Example 7 are as follows: Figure 3 As shown in the figure, the fatigue cycle number of the UV-resistant asphalt-based composite material under the two load strain loading modes of 2.5% and 5% is greatly increased compared with the matrix asphalt. Among them, with the increase of the dosage of UV-resistant additives, the fatigue cycle number gradually increases, and the fatigue resistance of the asphalt sample is enhanced.
[0096] Dynamic Shear Rheology Testing
[0097] The temperature of the UV-resistant asphalt-based composite materials obtained in Examples 4 to 7 was scanned before and after UV aging, and the aging factor calculation formula based on the modulus change was obtained. Figure 4 Compared with the base asphalt, the aging factor based on the modulus change of the UV-resistant asphalt-based composite material prepared by the present invention is lower within the test temperature range (40-80°C), indicating that the modulus of the UV-resistant asphalt-based composite material after UV aging is closer to that of the aged asphalt, and has excellent UV-resistant aging ability. As the dosage of the UV-resistant additive increases, the modulus aging factor gradually increases, and the UV resistance of the asphalt sample decreases.
[0098] Infrared spectrum test
[0099] The UV-resistant asphalt-based composite materials obtained in Examples 4 to 7 were tested by infrared spectroscopy before and after UV aging. The results are as follows: Figure 5 and Figure 6 According to the changes in the characteristic peak areas of carbonyl and sulfoxide groups in the infrared spectrum, the following Figure 7 The aging index (ICO and ISO) trend graph is shown. Compared with the base asphalt, the carbonyl aging index of the UV-resistant asphalt-based composite material prepared by the present invention is reduced by up to 32.47%, and the sulfoxide aging index is reduced by up to 20.38%, indicating that the addition of UV-resistant additives helps to improve the UV-resistant ability of asphalt samples.
[0100] Embodiment 8
[0101] The UV-resistant asphalt-based composite material of the present invention comprises a matrix asphalt and a UV-resistant additive, wherein the UV-resistant additive comprises graphite phase carbon nitride, a photoresponsive activity promoter, a compatibilizer and a pH regulator.
[0102] In this embodiment, the mass ratio of the base asphalt to the UV aging resistant additive is 92:8; the mass ratio of the graphite phase carbon nitride, the photoresponsive activity promoter, the compatibilizer and the pH adjuster is 70:15:14:1.
[0103] In this embodiment, the pH adjuster is concentrated ammonia water.
[0104] In this embodiment, the compatibilizer is dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride.
[0105] In this embodiment, the photoresponsive activity promoter includes bismuth vanadate and tourmaline powder, and the mass ratio of bismuth vanadate to tourmaline powder is 4:2.5.
[0106] The method for preparing the ultraviolet aging resistant asphalt-based composite material described in this embodiment comprises the following steps:
[0107] 1) Weighing matrix asphalt, graphite phase carbon nitride, photoresponsive active accelerator, compatibilizer and regulator;
[0108] 2) dissolving the phase carbon nitride and the photoresponsive activity promoter in an ethanol solution, and then performing ultrasonic dispersion to obtain a dark green solution;
[0109] 3) adding a pH adjuster dropwise to adjust the pH value of the solution, adding a compatibilizer, mechanically stirring, filtering and drying to obtain an anti-ultraviolet aging additive;
[0110] 4) The base asphalt is heated to 150° C., an anti-ultraviolet aging additive is added, and then high-speed shearing is performed at a rotation speed of 2000 rpm for 60 minutes to obtain an anti-ultraviolet aging asphalt-based composite material.
[0111] In this embodiment, the temperature of ultrasonic dispersion in step 2) is 25° C., and the ultrasonic dispersion time is 30 min.
[0112] In this embodiment, the temperature of mechanical stirring in step 3) is 40°C, and the temperature of drying treatment is 70°C.
[0113] In this embodiment, the mechanical stirring time in step 2) is 1 hour.
[0114] Embodiment 9
[0115] The UV-resistant asphalt-based composite material of the present invention comprises a matrix asphalt and a UV-resistant additive, wherein the UV-resistant additive comprises graphite phase carbon nitride, a photoresponsive activity promoter, a compatibilizer and a pH regulator.
[0116] In this embodiment, the mass ratio of the base asphalt to the UV aging resistant additive is 98:2; the mass ratio of the graphite phase carbon nitride, the photoresponsive activity promoter, the compatibilizer and the pH adjuster is 58:21.5:20:0.5.
[0117] In this embodiment, the pH adjuster is concentrated ammonia water.
[0118] In this embodiment, the compatibilizer is dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride.
[0119] In this embodiment, the photoresponsive activity promoter includes bismuth vanadate and tourmaline powder, and the mass ratio of bismuth vanadate to tourmaline powder is 4:3.
[0120] The method for preparing the ultraviolet aging resistant asphalt-based composite material described in this embodiment comprises the following steps:
[0121] 1) Weighing matrix asphalt, graphite phase carbon nitride, photoresponsive active accelerator, compatibilizer and regulator;
[0122] 2) dissolving the phase carbon nitride and the photoresponsive activity promoter in an ethanol solution, and then performing ultrasonic dispersion to obtain a dark green solution;
[0123] 3) adding a pH adjuster dropwise to adjust the pH value of the solution, adding a compatibilizer, mechanically stirring, filtering and drying to obtain an anti-ultraviolet aging additive;
[0124] 4) The base asphalt is heated to 160° C., an anti-ultraviolet aging additive is added, and then high-speed shearing is performed at a rotation speed of 2500 rpm for 90 minutes to obtain an anti-ultraviolet aging asphalt-based composite material.
[0125] In this embodiment, the temperature of ultrasonic dispersion in step 2) is 30° C., and the ultrasonic dispersion time is 35 min.
[0126] In this embodiment, the temperature of mechanical stirring in step 3) is 50°C, and the temperature of drying treatment is 80°C.
[0127] In this embodiment, the mechanical stirring time in step 2) is 2 hours.
[0128] Embodiment 10
[0129] The UV-resistant asphalt-based composite material of the present invention comprises a matrix asphalt and a UV-resistant additive, wherein the UV-resistant additive comprises graphite phase carbon nitride, a photoresponsive activity promoter, a compatibilizer and a pH regulator.
[0130] In this embodiment, the mass ratio of the base asphalt to the UV aging resistant additive is 95:5; the mass ratio of the graphite phase carbon nitride, the photoresponsive activity promoter, the compatibilizer and the pH adjuster is 63.5:25:10:1.5.
[0131] In this embodiment, the pH adjuster is concentrated ammonia water.
[0132] In this embodiment, the compatibilizer is dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride.
[0133] In this embodiment, the photoresponsive activity promoter includes bismuth vanadate and tourmaline powder, and the mass ratio of bismuth vanadate to tourmaline powder is 4:2.
[0134] The method for preparing the ultraviolet aging resistant asphalt-based composite material described in this embodiment comprises the following steps:
[0135] 1) Weighing matrix asphalt, graphite phase carbon nitride, photoresponsive active accelerator, compatibilizer and regulator;
[0136] 2) dissolving the phase carbon nitride and the photoresponsive activity promoter in an ethanol solution, and then performing ultrasonic dispersion to obtain a dark green solution;
[0137] 3) adding a pH adjuster dropwise to adjust the pH value of the solution, adding a compatibilizer, mechanically stirring, filtering and drying to obtain an anti-ultraviolet aging additive;
[0138] 4) The base asphalt is heated to 155° C., an anti-ultraviolet aging additive is added, and then high-speed shearing is performed at a rotation speed of 2300 rpm for 70 minutes to obtain an anti-ultraviolet aging asphalt-based composite material.
[0139] In this embodiment, the temperature of ultrasonic dispersion in step 2) is 28° C., and the ultrasonic dispersion time is 32 min.
[0140] In this embodiment, the temperature of mechanical stirring in step 3) is 45°C, and the temperature of drying treatment is 75°C.
[0141] In this embodiment, the mechanical stirring time in step 2) is 1.5 h.
[0142] Those skilled in the art will readily appreciate other embodiments of the present invention after considering the specification and disclosure of the invention. This application is intended to cover any variations, uses or adaptations of the present invention that follow the general principles of the present invention and include common knowledge or customary techniques in the art that are not disclosed by the present invention. The specification and examples are to be considered exemplary only, and the true scope and spirit of the present invention are indicated by the following claims.
[0143] It should be understood that the present invention is not limited to the exact construction that has been described above and shown in the drawings and that various modifications and changes may be made without departing from the scope thereof. The scope of the present invention is limited only by the appended claims.
[0144] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent structural change made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A UV-resistant asphalt-based composite material, characterized in that: It includes base asphalt and anti-ultraviolet aging additives, wherein the anti-ultraviolet aging additives include graphite phase carbon nitride, a photoresponsive activity promoter, a compatibilizer and a pH regulator.
2. The UV-resistant asphalt-based composite material according to claim 1, characterized in that: The mass ratio of base asphalt to UV-resistant aging additive is (92-98):(2-8); The mass ratio of graphite phase carbon nitride, photoresponsive activity promoter, compatibilizer and pH regulator is (58-70): (15-25): (10-20): (0.5-1.5).
3. The UV-resistant asphalt-based composite material according to claim 1, characterized in that: The pH regulator is concentrated ammonia water.
4. The UV-resistant asphalt-based composite material according to claim 1, characterized in that: The compatibilizer is dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride.
5. The UV-resistant asphalt-based composite material according to claim 1, characterized in that: The photoresponsive activity promoter includes bismuth vanadate and tourmaline powder, and the mass ratio of bismuth vanadate to tourmaline powder is 4:(2-3).
6. A method for preparing the UV-resistant asphalt-based composite material according to claim 1, characterized in that: The following steps are involved: 1) Weighing matrix asphalt, graphite phase carbon nitride, photoresponsive active accelerator, compatibilizer and regulator; 2) dissolving the phase carbon nitride and the photoresponsive activity promoter in an ethanol solution, and then performing ultrasonic dispersion to obtain a dark green solution; 3) adding a pH adjuster dropwise to adjust the pH value of the solution, adding a compatibilizer, mechanically stirring, filtering and drying to obtain an anti-ultraviolet aging additive; 4) The base asphalt is heated, and then an anti-ultraviolet aging additive is added, and then high-speed shearing is performed to obtain an anti-ultraviolet aging asphalt-based composite material.
7. The method for preparing the UV-resistant asphalt-based composite material according to claim 6, characterized in that: The temperature of ultrasonic dispersion in step 2) is 25-30°C, and the ultrasonic dispersion time is 30-35min.
8. The method for preparing the UV-resistant asphalt-based composite material according to claim 6, characterized in that: In step 3), the temperature of mechanical stirring is 40-50°C, and the temperature of drying treatment is 70-80°C.
9. The method for preparing the UV-resistant asphalt-based composite material according to claim 6, characterized in that: The mechanical stirring time in step 2) is 1-2h.
10. The method for preparing the ultraviolet aging resistant asphalt-based composite material according to claim 6, characterized in that: The specific process of step 4) is: The base asphalt is heated to 150-160° C., an anti-ultraviolet aging additive is added, and then high-speed shearing is performed at a rotation speed of 2000-2500 rpm for 60-90 minutes to obtain an anti-ultraviolet aging asphalt-based composite material.
Citation Information
Patent Citations
Application of carbon nitride nanosheet to improvement of ageing resistance of asphalt
CN107118575A